Pengaruh Lama Perebusan Terhadap Kadar Protein Tempe Kacang Tunggak (Vigna Unguiculata) - Halifah, Pagarra (Fakultas MIPA UNM, 2011)
This study was an experiment that aims to determine the effect of boiling time on protein content of cowpea tempe. This research was conducted in a laboratory experiment of Biology, MakassarÂ State University and in Central Laboratory of the Ministry of Health Makassar, Indonesia. The sample used cowpea tempe, made using 100 grams cowpea and 0,2 grams of tempe yeast for each sample, and got treatment without boiling as a control and variety of boiling time treatment for 2 minutes, 4 minutes and 6 minutes. This study used a complete randomized design (CRD) with 4 treatments and 3 replication. Determination of protein content by Kjeldahl method. The results showed that the effect of boiling time was very real (PË‚0,05) for protein content, where the highest protein levels found in the treatment of boiling for 2 minutes (8,50). It was comparable with boiling for 4 minutes and 6 minutes, but did not different from the control. The lowest protein content was found in boiling treatment for 6 minutes (4,76). So it can be concluded that the longer time boiling, then lower protein content.Â